The impact of previous open abdominal surgery on the outcome of laparoscopic colorectal surgery (Annals of Medical Research, 2021)
Aim: Although the laparoscopic approach is increasingly being used in colorectal surgery, it is anticipated that the technical problems caused by previous abdominal open surgery (PAOS) will adversely affect the outcomes. The aim of this study was to evaluate the outcomes of previous abdominal surgery in patients with colorectal cancer who underwent laparoscopic surgery for treatment.Material and Methods: Among the patients who underwent laparoscopic surgery for colorectal cancer between January 2015 and December 2018, those who had a history of previous abdominal surgery and those who did not were compared. Those with a history of laparoscopic abdominal surgery are not included in the PAOS group and short-term postoperative complications, conversion to open surgery, reoperations, hospital readmissions, and mortality rates were analyzed between the groups.Results: 21 of 140 patients who underwent laparoscopic surgery for colorectal cancer had PAOS. The groups with and without PAOS were similar in terms of age, sex, body mass index, ASA score, and comorbid disease. No difference was observed regarding conversion to open surgery (p = 0.513), postoperative complications (p> 0.05), reoperations (p = 0.162), unplanned hospital readmissions (p = 0.154), and perioperative mortality (p = 0.136) between the two groups.Conclusion: We believe that laparoscopy can be safely performed in patients with colorectal cancer who had previous abdominal open surgery with similar clinical and postoperative complication rates as in patients without a history of PAOS.
Keywords: Adhesions; colon cancer; laparoscopic surgery; postoperative complications; rectal cancer